Noninvasive Stool Antigen Assay for Screening of Helicobacter Pylori Infection and Assessing Success of Eradication Therapy in Patients on Hemodialysis (Iranian Journal of Kidney Diseases, 2010)
Introduction. Helicobacter pylori infection can be diagnosed by biopsy-based or noninvasive methods. Our aim was to identify H pylori-positive patients on hemodialysis by the noninvasive method of H pylori stool antigen (HPSA) and investigate its diagnostic accuracy for assessment of the eradication of infection after treatment in comparison with urea breath test (UBT).Materials and Methods. Serology, HPSA, and UBT were performed on 87 hemodialysis patients. Infection with H pylori was confirmed if at least 2 tests were positive. Patients with H pylori infection received a 2-week course of triple therapy. To evaluate success of eradication HPSA and UBT were done after 8 weeks.Results. Eighty-seven patients were enrolled in the study, of whom 39 (44.8%) were proved to have H pylori infection. The HPSA was positive in the stool specimens of 37 patients (42.5%) and the serology test was positive in 39 (44.8%). The HPSA had a 87.1% sensitivity and a 93.7% specificity for detection of H pylori infection. Thirty-seven patients completed the treatment period. Success of H pylori eradication was documented in 30 of the 37 patients (81.1%) based on UBT. After the treatment, the HPSA was negative in 32 of 37 of the stool specimens (86.4%), showing a 42.8% sensitivity and a 93.3% specificity to detect the failure of eradication of H pylori.Conclusions. Helicobacter pylori stool antigen assay is a noninvasive reliable tool to screen H pylori infection before therapy and assess the success of eradication in patients on hemodialysis.